Meta‐Fish‐Lib : A generalised, dynamic DNA reference library pipeline for metabarcoding of fishes - Rupert A. Collins; Giulia Trauzzi; Katherine M. Maltby; Thomas I. Gibson; Frances C. Ratcliffe; Jane Hallam; Sophie Rainbird; James Maclaine; Peter A. Henderson; David W. Sims; Stefano Mariani; Martin J. Genner (Journal of Fish Biology, 2021)
The accuracy and reliability of DNA metabarcoding analyses depend on the breadth and quality of the reference libraries that underpin them. However, there are limited options available to obtain and curate the huge volumes of sequence data that are available on public repositories such as NCBI and BOLD. Here, we provide a pipeline to download, clean and annotate mitochondrial DNA sequence data for a given list of fish species. Features of this pipeline include (a) support for multiple metabarcode markers; (b) searches on species synonyms and taxonomic name validation; (c) phylogeny assisted quality control for identification and removal of misannotated sequences; (d) automatically generated coverage reports for each new GenBank release update; and (e) citable, versioned DOIs. As an example we provide a ready‐to‐use curated reference library for the marine and freshwater fishes of the U.K. To augment this reference library for environmental DNA metabarcoding specifically, we generated 241 new MiFish‐12S sequences for 88 U.K. marine species, and make available new primer sets useful for sequencing these. This brings the coverage of common U.K. species for the MiFish‐12S fragment to 93%, opening new avenues for scaling up fish metabarcoding across wide spatial gradients. The Meta‐Fish‐Lib reference library and pipeline is hosted at https://github.com/genner-lab/meta-fish-lib .